PHYSICAL STABILITY STUDY OF OINTMENT FROM LEAF EXTRACT OF TEKELAN (Chromolaena odorata L.) ON VARIOUS TYPES OF BASES - Susanti; Wahida Hajrin; Nisa Isneni Hanifa (Faculty of Medicine Universitas Mataram, 2022)
Tekelan (C. odorata) contains phenolic compounds that play an important role in wound healing. The potential of C. odorata leaves as a wound healer needs to be developed through the formulation of ointment to facilitate its use. The selection of ointment base will affect the effectiveness. The aim of this study was to determine the physical stability of ointment from C. odorata leaf extract on varios types of bases. The ointment of C. odorata leaf extract with four types of bases, i.e hydrocarbon base (F1), adsorption base (F2), washable base (F3), and water soluble base (F4) were tested for stability using mechanichal method and freeze-thaw cycle. Mechanichal stability test was carried out by centrifuging the samples at a speed 3750 rpm for 30 menutes, while the freeze-thaw cycle test was carried out for 12 days (6 cycles). The physical properties of ointment i.e organoleptics, homogeneity, pH, spreadability, and sticky power before and after the test were compared by ANOVA. The result of mechanichal test of ointment showed that there is no separation in all types of bases. Stability test by freeze-thaw cycle method indicated a change of homogeneity and organoleptic of F1 and F2. Spreadability of all formulas was not significantly different before and after the freeze-thaw cycle, while the stable sticky power only occurred at F4 (p-value=0.523). Formula F4 which is an ointment of C. odorata leaf extract with a water soluble base has the best stability among other bases.